Performance Advantages of Left-Handed Cricket Batting Talent - Connor, Jonathan D.; Mann, David L.; Gomez, Miguel-Angel; Leicht, Anthony S.; Doma, Kenji (Frontiers in Psychology, 2020)
The purpose of this study was to examine performance advantages associated with batting stance, in the form of left- versus right handed dominant stance, and orthodox versus reverse stance, of talented junior cricket batters within age-restricted competitions. Data were sourced from the National male younger age competition (YAC; Under-17; n=237) and older-age competition (OAC; Under-19; n=302), as well as female younger age competition (YAC; Under-15; n=234) and older-age competition (OAC; Under-18; n=260) over a four year period. Left-hand dominant (LHD) batters were consistently overrepresented in the male YAC (Right: 69.2%; Left: 30.8%) and OAC (Right: 68.2%; Left: 31.8%) compared with the expected general population distribution. Male LHD batters exhibited a significantly (p<0.05) higher batting aggregate (YAC: 116.82 ±84.75 vs. 137.84 ±89.74; OAC: 117.07 ±89.00 vs. 146.28 ±95.99), scored more runs (YAC: 19.65 ±12.32 vs. 23.96 ±14.71; OAC: 19.27 ±12.61 vs. 23.98 ±14.15), spent more time batting (YAC: 45.33 ±25.89mins vs. 54.59 ±28.62mins; OAC: 39.80 ±21.79mins vs. 49.33 ±27.41mins), and scored more boundary-4s per game (YAC: 1.83 ±1.40 vs. 2.44 ±1.87; OAC: 1.76 ±1.32 vs. 2.19 ±1.83), across both YAC and OAC groups with small effects sizes. No overrepresentation was present for either female group (YAC, Right: 88.5%/ Left: 11.5%; OAC, Right: 90.0%/ Left: 10.0%). Female LHD batters exhibited significantly higher batting aggregate (68.97 ±53.17 vs. 102.96 ±73.48), batting average (13.24 ±10.88 vs. 17.75 ±12.28), and spent more time batting per game (25.52 ±15.08mins vs. 37.75 ±26.76mins); however, only at the OAC level with small-moderate effects sizes. Finally, there were few performance advantages identified to batting with a reverse stance, with further work needed to clarify any potential biomechanical benefits. Team selection practices may exploit the left-handed advantage by over-selecting talented left-handed junior cricketers. Practical implications for coaches include creating practice environments that negate the negative frequency-dependent selection, such as providing more practice opportunities for their players against left-handed opponents.